2014
DOI: 10.1186/s40348-014-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer therapy: know your enemy?

Abstract: BackgroundMost cancer therapies are devised for adult or even elder patients. However, when dealing with pediatric cancers, additional considerations are needed.ConclusionsThis review discusses non-classic components of tumors and highlights possible treatment approaches which might be of particular benefit for children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Therefore, major attention was focused on the study of the role of tumor microenvironment (TME) not only in tumor initiation but also in progression and metastasis. The hypothesis of cancer cell development and proliferation only in a conducive environment has been made by Paget since 1889 [308]. While Paget suggested that the microenvironment facilitates or inhibits metastasis through growth-promoting/ inhibiting factors, recent research sustains that the tumor is directed into one or several possible molecular evolution pathways by signals originating in native and/or modified microenvironmental factors [309].…”
Section: The Roles Of Microenvironment-mediated Epigenetic Perturbatimentioning
confidence: 99%
“…Therefore, major attention was focused on the study of the role of tumor microenvironment (TME) not only in tumor initiation but also in progression and metastasis. The hypothesis of cancer cell development and proliferation only in a conducive environment has been made by Paget since 1889 [308]. While Paget suggested that the microenvironment facilitates or inhibits metastasis through growth-promoting/ inhibiting factors, recent research sustains that the tumor is directed into one or several possible molecular evolution pathways by signals originating in native and/or modified microenvironmental factors [309].…”
Section: The Roles Of Microenvironment-mediated Epigenetic Perturbatimentioning
confidence: 99%
“…27 This approach resulted in a considerable life extension in the experimental animals compared with standard therapy andinterestingly -resulted in increasingly longer gaps between treatments as time progressed. 27 While generally speaking, a chronifying approach does not lend itself to pediatric cancers, 16 it is, however, a variant thereof that shows clinical promise in the treatment of childhood glioblastoma.…”
Section: New Therapeutic End Pointsmentioning
confidence: 99%
“…16 However, even with treatment success, long-term adverse effects and treatment-induced secondary cancers are, with extended life expectancies, also becoming increasingly a problem. 16 Recent advances in the analysis of whole cancer genomes and protein expression patterns, 17 combined with the increasing acceptance DOI: 10.17925/EOH.2014. 10.2.116 of the cancer stem cell model 18 and increasing appreciation of the tumour microenvironment, 15 have put to rest the notion of tumours as monolithic entities.…”
mentioning
confidence: 99%